(untitled) (Bangladesh Journal of Medical Science, 2014)
Objective: Information is very important to have accurate understanding of people about the modes of HIV/AIDS transmission and its prevention strategies. Teachers at all levels are always expected to play a foremost role in the provision of information to promote awareness leading to behavioral change among students. Therefore, this article is aimed to evaluate the knowledge, awareness and perception about the deadly disease HIV/AIDS among primary school teachers in Bangladesh. Materials and methods: To do so, about 120 teachers from 28 primary schools, out of 68, in Rajshahi City Corporation (RCC) areas were interviewed purposively for this study using a self-administered questionnaire. Results and discussion: The results showed that the teachers serving at primary schools level were not too sure of their own knowledge about the issue. They had much misperception about the knowledge of facts, modes of transmission to reduce contamination and the modes of transmission from one person to another of HIV/AIDS. Conclusion: Government should provide adequate funding to organize and sponsor teachers to attend in training workshops, seminars and conferences related to HIV/AIDS and that the pandemic should be discussed with other for the purpose of awareness. DOI: http://dx.doi.org/10.3329/bjms.v13i2.18297 Bangladesh Journal of Medical Science Vol.13(2) 2014 p.145-149